Pengaruh Kelengkapan Fitur Aplikasi, Kemudahan Transaksi, Dan Potongan Harga Terhadap Keputusan Pembelian Tiket Bioskop Pada Aplikasi TIX ID - Muhammad Irsyad Fauzan; Sujana Sujana (LPPM IBI Kesatuan, 2022)
The era of modernization is now increasingly demanding people to adapt to all forms of technology, one of which is a businessman. Many business people are competing to use the internet to promote their business. This study discusses the use of the TIX ID application which also presents the digital world in ordering cinema tickets online. The purpose of this study was to determine: 1) the effect of the completeness of the application features on the purchase decision of cinema tickets on the TIX ID application in the city of Bogor, 2) the effect of ease of transaction on the decision to purchase a cinema ticket on the TIX ID application in the city of Bogor, 3) the effect of price discounts on the purchase decision of cinema tickets on the TIX ID application in the city of Bogor, 4) the effect of the completeness of the application features, ease of transactions, and price discounts affect the purchase decision. This study uses independent variables (completeness of application features, ease of transaction, and discounted prices) and the dependent variable (purchase decision). The method used in this research is a quantitative approach. With a total of 215 respondents selected were TIX ID application users in the city of Bogor. To analyze and process data, this study uses LISREL version 8.80 and SPSS version 23. Based on the research, it can be concluded that; 1) completeness of the application features has a positive and significant effect on purchasing decisions by 31% with the acquisition of t-count 4.42, 2) ease of transaction has a positive and significant effect on purchasing decisions by 32% with the acquisition of t-count 4.75, 3) the price discount has a positive effect and significant to the purchase decision of 45% with the acquisition of t-count 2.82, 4) the completeness of the application features, ease of transaction, and discounted prices simultaneously influence the purchase decision of 89%. Keywords: Completeness of Application Features, Ease of Transaction, Discounted Prices, Purchasing Decision